Nanometer scale fabrication and optical response of InGaN/GaN quantum disks. (15th September 2016) - Lai, Yi-Chun; Higo, Akio; Kiba, Takayuki; Thomas, Cedric; Chen, Shula; Lee, Chang Yong; Tanikawa, Tomoyuki; Kuboya, Shigeyuki; Katayama, Ryuji; Shojiki, Kanako; Takayama, Junichi; Yamashita, Ichiro; et al.
Abstract: In this work, we demonstrate homogeneously distributed In0.3 Ga0.7 N/GaN quantum disks (QDs), with an average diameter below 10 nm and a high density of 2.1 × 10 11 cm −2, embedded in 20 nm tall nanopillars. The scalable top-down fabrication process involves the use of self-assembled ferritin bio-templates as the etch mask, spin coated on top of a strained In0.3 Ga0.7 N/GaN single quantum well (SQW) structure, followed by a neutral beam etch (NBE) method. The small dimensions of the iron cores inside ferritin and nearly damage-free process enabled by the NBE jointly contribute to the observation of photoluminescence (PL) from strain-relaxed In0.3 Ga0.7 N/GaN QDs at 6 K. The large blueshift of the peak wavelength by over 70 nm manifests a strong reduction of the quantum-confined Stark effect (QCSE) within the QD structure, which also agrees well with the theoretical prediction using a 3D Schrödinger equation solver. The current results hence pave the way towards the realization of large-scale III-N quantum structures using the combination of bio-templates and NBE, which is vital for the development of next-generation lighting and communication devices.